The people vs. coke - Barry, Daniel; BBC worldwide (North Sydney, N.S.W. : BBC Worldwide, 2003)
This BBC documentary explores the stunning mid-'80s failure that was New Coke and explains how the product came to be and the army of Coke enthusiasts that launched campaigns that forced the company to return to its roots
Title from title screen
Executive producer, Bill Grist
Narrator: Jim Carter
DVD format
Keywords: Coca-Cola Company -- History; Soft drink industry -- History